Assessment of two seed technologies for the direct seeding of Festuca pallescens, a key species for grassland restoration in Patagonia - Martin Albarracin, Valeria Leticia; Easdale, Marcos Horacio; Angeli, Juan Pablo; Hurtado, Santiago Ignacio; Ignazi, Griselda; Lopez, Aldana Soledad; Guidalevich, Verónica; Marchelli, Paula (Wiley, 2025)
Direct seeding of native species is a practice with high potential for the restoration of degraded areas. Since the availability of seeds of native species is often limited, it is necessary to make the most of this resource. In this work, we tested two different technologies for the direct seeding of Festuca pallescens: seed coating and hydrogel soil amendment. For this, we conducted two greenhouse trials under controlled conditions and five field sowing trials in two different environments that differ in mean annual precipitation and in different seasons (autumn and spring). The greenhouse trials consisted of (1) seeding natural seeds in two substrates (soil with vs. without hydrogel) and under two irrigation regimes (regular irrigation vs. water restriction regime); (2) seeding differently treated seeds (natural vs. coated) under water restriction regime in two substrates (soil with vs. without hydrogel). Field trials consisted of seeding differently treated seeds (natural vs. coated) under natural rainfall conditions in two substrates (soil with vs. without hydrogel). Greenhouse trials showed that hydrogel soil amendment increased soil relative humidity and promoted growth under a water restriction regime. Field trials showed mixed results: hydrogel often reduced seedling emergence, while seed coating enhanced emergence when seeding immediately after coating treatment but not thereafter. Autumn planting emerged as the optimal season for F. pallescens, correlating with higher emergence and improved survival 1 year post-planting. Site-specific differences were also observed, highlighting habitat suitability variability. Overall, these technologies exhibited context-dependent effects, suggesting nuanced recommendations for their application in ecological restoration efforts.